2013
DOI: 10.1177/2049463713516755
|View full text |Cite
|
Sign up to set email alerts
|

New approaches towards chronic pain: patient experiences of a solution-focused pain management programme

Abstract: Research has suggested that Solution-Focused Brief Therapy (SFBT) may be effective in facilitating meaningful change for those living with chronic pain. This study aimed to further this understanding through exploring the experiences of people living with chronic pain, who had attended an 8-week solution-focused pain management programme. The design of this study was conducted in consultation with a service-user advisory group, and employed a qualitative and interpretative design rooted in critical community p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…39,40 Preliminary outcome data from the PMP delivered by the SF-informed pain management service have suggested statistically and clinically significant improvements in self-efficacy, functioning and wellbeing, 41 along with psychological and behavioural improvements which enabled individuals 'to live better in the presence of pain'. 42 While the evidence for SF PMPs is limited at present, these studies indicate growing support for this approach. Fundamentally, SF principles reflect PMP guidance 30 which stipulates that these programmes should enable individuals to 'live well' despite chronic pain by supporting them to develop self-management plans based on personal resources.…”
Section: Psychosocial Management Of Chronic Painmentioning
confidence: 93%
“…39,40 Preliminary outcome data from the PMP delivered by the SF-informed pain management service have suggested statistically and clinically significant improvements in self-efficacy, functioning and wellbeing, 41 along with psychological and behavioural improvements which enabled individuals 'to live better in the presence of pain'. 42 While the evidence for SF PMPs is limited at present, these studies indicate growing support for this approach. Fundamentally, SF principles reflect PMP guidance 30 which stipulates that these programmes should enable individuals to 'live well' despite chronic pain by supporting them to develop self-management plans based on personal resources.…”
Section: Psychosocial Management Of Chronic Painmentioning
confidence: 93%
“…Two studies (Dargan et al 2014;Larsen et al 2015) reported qualitative themes which reflected improvements relevant to positive psychological constructs (e.g., flourishing). Dargan et al (2014) described themes relating to participants' experiences of attending a PPI.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Two studies (Dargan et al 2014;Larsen et al 2015) reported qualitative themes which reflected improvements relevant to positive psychological constructs (e.g., flourishing). Dargan et al (2014) described themes relating to participants' experiences of attending a PPI. One theme (i.e., 'Accessing the programme') reflected the initial effects that being invited to take part in the PPI had upon the individual, in terms of inducing a feeling of hope within participants that the intervention may lead to increased sense of control and greater independence.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Another problem related to the current model of care in chronic pain refers to decision-making in the face of unwanted events. Specifically, the current approach to care requires patients to judge when an undesired event is problematic and what is the preferred action to take in the face of that event [ 30 , 31 , 32 ]. This approach is problematic, as some patients may tolerate serious or even urgent problems (e.g., tachycardia, severe drowsiness, or persistent vomiting, diarrhea or urine retention) for too long, while others may seek care for symptoms that are less urgent or not problematic (e.g., very mild or short-term).…”
Section: Introductionmentioning
confidence: 99%